Freud and psychoanalysis/ Translated by R.F.C. Hull. - "Jung, C.G." (London, 1981)
Freud was one of the giants of 20th century thought. His ideas have been hugely influential not only in psychology but in all the social sciences and the arts. Even those who have never read a word of his writings are familiar with his concepts of the id, the ego, the Oedipus complex and the workings of the unconscious mind.
Keywords: Psychology